How motion planning affects human factors in human-robot collaboration. Issue 5 (2020) - Beschi, Manuel; Faroni, Marco; Copot, Cosmin; Pedrocchi, Nicola
Abstract: Dependability of robot co-workers plays an important role in increasing the effectiveness of human-robot interaction in manufacturing. Our goal is to understand the role of motion planning parameters in human-robot collaboration and to provide guidelines for the selection of the most suitable motion planner. The human factors analysis provided in this paper highlights that repeatability of the motion and predictability of the robot timing affect the quality of human-robot collaboration.